Constraints on the vital effect in coccolithophore and dinoflagellate calcite by oxygen isotopic modification of seawater - Hermoso, M; Horner, T; Minoletti, F; Rickaby, R (Elsevier, 2014)
In this study, we show that there are independent controls of 18O/16O and 13C/12C fractionation in coccolithophore and dinoflagellate calcite due to the contrasting kinetics of each isotope system. We demonstrate that the direction and magnitude of the oxygen isotope fractionation with respect to equilibrium is related to the balance between calcification rate and the replenishment of the internal pool of dissolved inorganic carbon (DIC). As such, in fast growing cells, such as those of Emiliania huxleyi and Gephyrocapsa oceanica (forming the so-called "heavy group"), calcification of the internal carbon pool occurs faster than complete isotopic re-adjustment of the internal DIC pool with H2O molecules. Hence, coccoliths reflect the heavy oxygen isotope signature of the CO2 overprinting the whole DIC pool. Conversely, in large and slow growing cells, such as Coccolithus pelagicus ssp. braarudii, complete re-equilibration is achieved due to limited influx of CO2 leading to coccoliths that are precipitated in conditions close to isotopic equilibrium ("equilibrium group"). Species exhibiting the most negative oxygen isotope composition, such as Calcidiscus leptoporus ("light group"), precipitate coccolith under increased pH in the coccolith vesicle, as previously documented by the "carbonate ion effect". We suggest that, for the carbon isotope system, any observed deviation from isotopic equilibrium is only "apparent", as the carbon isotopic composition in coccolith calcite is controlled by a Rayleigh fractionation originating from preferential incorporation of 12C into organic matter. Therefore, species with low PIC/POC ratios as E. huxleyi and G. oceanica are shifted towards positive carbon isotope values as a result of predominant carbon fixation into the organic matter. By contrast, cells with higher PIC/POC as C. braarudii and C. leptoporus maintain, to some extent, the original negative isotopic composition of the CO2. The calcareous dinoflagellate Thoracosphaera heimii exhibits different behaviour for both isotopic systems, in particular with respect to its very negative carbon isotope composition, owing to coeval intra and extracellular biomineralisation in this group. In this study, we also investigate the sensitivity of 18O/16O fractionation to varying ambient oxygen isotope composition of the medium for inorganic, coccolithophore, and dinoflagellate calcite precipitated under controlled laboratory conditions. The varying responses of different taxa to increased oxygen isotope composition of the growth medium may point to a potential bias in sea surface temperature reconstructions that are based on the oxygen isotopic compositions of sedimentary calcite, especially during times of changing seawater oxygen isotopic composition. Overall, this study represent an important step towards establishing a mechanistic understanding of the "vital effect" in coccolith and dinoflagellate calcite, and provides valuable information for interpreting the geochemistry of the calcareous nannofossils in the sedimentary record, at both monospecific and interspecies levels.